2019
DOI: 10.3389/fmicb.2019.00886
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nipah Virus Codon Usage and Adaptation to Hosts

Abstract: A recent outbreak of Nipah virus (NiV) in India has caused 17 deaths in people living in districts of Kerala state. Its zoonotic nature, as well as high rate of human-to-human transmission, has led researchers worldwide to work toward understanding the different aspects of the NiV. We performed a codon usage analysis, based on publicly available nucleotide sequences of NiV and its host adaptation, along with other members of the Henipavirus genus in ten hosts. NiV genome encodes nine ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(150 citation statements)
references
References 84 publications
10
139
0
1
Order By: Relevance
“…When evaluated in terms of their ENc value, the 44 viral genomes all lacked a strong codon bias. This result is consistent with the codon usage in most RNA viruses, such as the Citrus tristeza virus [35], Enterovirus [36], Hendra virus [37], and Nipah virus [38], in that they all lacked a strong codon bias. A possible explanation for the weak codon bias is that it is advantageous for efficient replication, re-adaption, and survival in host cells [39,40].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…When evaluated in terms of their ENc value, the 44 viral genomes all lacked a strong codon bias. This result is consistent with the codon usage in most RNA viruses, such as the Citrus tristeza virus [35], Enterovirus [36], Hendra virus [37], and Nipah virus [38], in that they all lacked a strong codon bias. A possible explanation for the weak codon bias is that it is advantageous for efficient replication, re-adaption, and survival in host cells [39,40].…”
Section: Discussionsupporting
confidence: 82%
“…A possible explanation for the weak codon bias is that it is advantageous for efficient replication, re-adaption, and survival in host cells [39,40]. The similarity index R(A,B) has been widely used to represent the degree of similarity between a virus and its host, with respect to their overall codon usage patterns, and to further evaluate the potential role of the overall codon usage patterns of the host in the formation of the overall codon usage of a virus [25,38]. We used this index to infer the similarity between host-taxa-groups and found that all of the similarity values were at higher levels.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the CAI value the higher the gene expression, and vice versa. The 13 SARS-CoV-2 isolates used in the analysis showed an overall average CAI value of 0.54 ± 0.0003 for the complete coding region, which is comparatively slightly lower than the CAI values of viruses from other studies in relation to Homo sapiens, indicating moderate SARS-CoV-2 adaptation to Homo sapiens (Butt et al, 2016;Khandia et al, 2019;Kumar et al, 2018). However, at the individual genes level, different CAI values have been observed.…”
Section: Moderate Adaptation Of Sars-cov-2 To Homo Sapiensmentioning
confidence: 77%
“…Codon usage vari-ation occurs may be due to natural selection and/or mutation pressure for accurate and efficient translation in various organisms [19,20]. Differences in the frequency of occurrence on synonymous codons in coding DNA is termed as synonymous codon usage bias [32].…”
Section: Data Acquisition and Processingmentioning
confidence: 99%